Deciphering tourist shoppers’ U-commerce readiness: Current challenges and post-pandemic concerns - Loh, E. G. Y. *; Stephenson, M. L. * (South Asia Publications, 2021)
Increased reliance and advancements in technology and a change of behavior amongst tourist shoppers due to the pandemic indicate the need to reconsider U-commerce technologies and applications, ensuring that the retailing industry is sustainable. Prior to the COVID-19 pandemic it was not uncommon for shopping activities to be mediated by technology applications. However, the pandemic arguably improved consumers’ comprehension and confidence of technological functionalities as shopping technology applications were increasingly embedded into individual lifestyles, especially as national populations have been under periodic lockdowns and restricted mobility. Few inquiries have focused on U-commerce implications as a consequence of COVID-19 and seriously contemplated potential implications for the post-pandemic era, particularly in the field of tourism retail. Accordingly, key conceptual U-commerce technology applications and industry practices are presented, especially those based on four U-tourism marketing strategies: nexus marketing; transformation marketing; sync marketing; and immersive marketing. The discussion also involves U-tourism marketing strategies which could be applied to tourism retailing in the post-COVID-19 era, further evaluating U-commerce challenges for tourist shoppers in adapting to the digital economy. The work finally indicates the implications concerning the need for practitioners to operationalize U-commerce technologies to cater to the “new wave” of tourist shoppers